Anti-aging low-temperature-resistant glue as well as preparation method and application thereof

By adding castor oil, 2-hydroxyethyl ricinoleate and TDI-modified Ti3C2Tx/MoS2 composite materials to the glue, the problem of reduced viscosity and insufficient mechanical properties of the glue in low temperature environment is solved, and the glue is high low temperature resistance and strong mechanical properties are achieved.

CN119842357AActive Publication Date: 2025-04-18XIAN SENYOU ELECTRONIC TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510141102.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-18
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The existing glue has reduced viscosity in low temperature environments and insufficient mechanical properties, making it difficult to meet the requirements of low temperature resistance for a wide range of applications.

Method used

The low temperature resistance and mechanical properties of the glue are improved by adding castor oil and 2-hydroxyethyl ricinoleate to the glue, combined with the TDI-modified Ti3C2Tx/MoS2 composite.

Benefits of technology

It significantly improves the low-temperature resistance and mechanical properties of the glue, so that it still maintains excellent viscosity and strength in low-temperature environments, and is suitable for a wide range of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005264887940000071
    Figure BDA0005264887940000071
  • Figure BDA0005264887940000081
    Figure BDA0005264887940000081
Patent Text Reader

Abstract

The invention belongs to the technical field of adhesives, and particularly relates to anti-aging and low-temperature-resistant glue as well as a preparation method and application thereof. The adhesive comprises the following components in parts by weight: 60-80 parts of isocyanate; 70 to 90 parts of polyether polyol; 3 to 7 parts of a TDI modified Ti < 3 > C < 2 > T < x > / MoS2 composite material; 3-5 parts of castor oil; 1 to 3 parts of 2-hydroxyethyl ricinoleate; 30-40 parts of a plasticizer; 3 to 5 parts of dibutyltin dilaurate; 4-8 parts of a silane coupling agent; and 1-3 parts of an anti-aging agent. The castor oil and the 2-hydroxyethyl ricinoleate are added into the glue and compounded, so that the low-temperature resistance of the glue is improved, and the mechanical property of the glue is improved in cooperation with the TDI modified Ti3C2Tx / MoS2 composite material. The anti-aging low-temperature-resistant glue prepared by the invention is excellent in performance and wide in application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adhesives, and more specifically, relates to an anti-aging and low-temperature resistant glue and a preparation method and application thereof. Background Art

[0002] Polyurethane adhesives have excellent properties such as anti-shear, anti-peel, and low-temperature resistance, and are suitable for bonding most structural parts. Polyurethane adhesives are a type of adhesive that produces viscosity by reacting the excess -NCO active groups in the polymer with the free active hydrogen in the air or on the substrate. Since the temperature of polyurethane adhesives will affect their viscosity, the low-temperature resistance of polyurethane adhesives is improved by adding modified components.

[0003] CN113897166A discloses a two-component polyurethane glue, which includes a component A and a component B, wherein the component A includes the following raw materials: isophorone diisocyanate; polyester polyol; ethylenediamine; catalyst; the component B includes the following raw materials: butyl rubber; N-(pyridin-4-yl-methylene)methylamine; 4'-methoxyphenyl butanone; dextrin palmitate; bridging agent; a method for preparing a two-component polyurethane glue, wherein the component A and the component B are prepared separately and then blended to obtain the glue. The application has the following effects: the polyurethane resin has a high molecular weight, a complex grafting structure, and high strength after curing; the butyl rubber can improve the bonding strength and cold resistance; the steric hindrance of N-(pyridin-4-yl-methylene)methylamine can constrain the diffusion movement of the chain segment to increase the viscosity of the system; by mixing 4'-methoxyphenyl butanone and dextrin palmitate, a cross-linking reaction is generated in the presence of a bridging agent to form a macromolecular cross-linking structure, which effectively improves the cold resistance and solvent resistance of the glue.

[0004] CN108165226A discloses a polymer for electronic potting glue and a preparation method thereof. The polymer for electronic potting glue is made of the following raw materials in weight percentage: 10-35% isocyanate, 0-20% polyester polyol, 10-40% polyether polyol, 40-50% solvent, and 0.1-0.3% catalyst. The electronic potting glue prepared by the present invention has a long storage time, good yellowing resistance after curing, high strength, and strong adhesion to electronic devices. It has good fluidity and is easy to operate during production operation. After being coated on electronic devices, it reacts gently without generating bubbles, and the product has good transparency after curing.

[0005] CN115820195A discloses a polyurethane glue for high-brightness reflective materials, and the raw materials for preparation include, by weight: 20-50 parts of polyester polyol, 1-10 parts of carboxylic acid compound, 5-15 parts of isocyanate, 0.01-0.2 parts of catalyst, 50-70 parts of solvent, and 0-0.05 parts of terminator. The present invention uses low-crystallinity polyester polyol formed by polymerization of succinic acid and 3-methyl-1,5-pentanediol as the polyurethane glue base material, which can improve the water washing resistance, dry cleaning resistance, grease resistance, and sweat resistance of the polyurethane glue. In addition, by using dihydroxypropyl butyric acid to react with low-crystallinity polyester polyol, the creep resistance of the polyurethane glue layer can be improved, and the reflective particles will not sink in the reflective product, and the reflective product has good wear resistance and can be bent multiple times without cracking in a low-temperature environment.

[0006] By adding modified components to the glue or modifying the raw materials themselves, the glue can be improved to still have excellent mechanical properties at low temperatures. The present invention provides an anti-aging and low-temperature resistant glue with excellent low-temperature resistance and mechanical properties. Summary of the invention

[0007] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide an anti-aging and low-temperature resistant glue and its preparation method and application. The following components are included by weight: 60-80 parts of isocyanate; 70-90 parts of polyether polyol; TDI modified Ti 3 C 2 T x / MoS 2 3-7 parts of composite material; 3-5 parts of castor oil; 1-3 parts of 2-hydroxyethyl ricinoleate; 30-40 parts of plasticizer; 3-5 parts of dibutyltin dilaurate; 4-8 parts of silane coupling agent; 1-3 parts of anti-aging agent. The present invention improves the low temperature resistance of the glue by adding castor oil and 2-hydroxyethyl ricinoleate to the glue, and the low temperature resistance of the glue is improved by combining the two. 3 C 2 T x / MoS 2 The composite material improves the mechanical properties of the glue. The anti-aging and low-temperature resistant glue prepared by the invention has excellent performance and is widely used.

[0008] The purpose of the invention is to provide an anti-aging and low-temperature resistant glue.

[0009] Another object of the present invention is to provide a method for preparing anti-aging and low-temperature resistant glue.

[0010] Another object of the present invention is to provide an application of anti-aging and low-temperature resistant glue.

[0011] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0012] An anti-aging and low-temperature resistant glue, comprising the following components by weight:

[0013] 60-80 parts of isocyanate;

[0014] 70-90 parts of polyether polyol;

[0015] TDI modified Ti 3 C 2 T x / MoS 2 3-7 parts of composite material;

[0016] 3-5 parts of castor oil;

[0017] 1-3 parts of 2-hydroxyethyl ricinoleate;

[0018] 30-40 parts of plasticizer;

[0019] 3-5 parts of dibutyltin dilaurate;

[0020] Silane coupling agent 4-8 parts;

[0021] 1 to 3 parts of anti-aging agent.

[0022] Preferably, the isocyanate is diphenylmethane-4,4′-diisocyanate; and the polyether polyol is polyether polyol 450.

[0023] Further preferably, the plasticizer is phthalate; the silane coupling agent is KH-560; and the anti-aging agent is antioxidant 1010.

[0024] In the present invention, the preferred embodiment is that the TDI-modified Ti 3 C 2 T x / MoS 2 The method for preparing the composite material comprises the following steps:

[0025] (1) Etching Ti with concentrated HF solution 3 AlC 2 Precursor, get Ti 3 C 2 T x Dispersion, separation, washing, drying to Ti 3 C 2 T x ;

[0026] (2) Ti obtained in step (1) 3 C 2 T xDisperse in deionized water, sonicate for 20-40 minutes, then add molybdate and continue sonication for 10-20 minutes, then add sulfur source and continue sonication for 10-30 minutes, then transfer to a hydrothermal reactor lined with polytetrafluoroethylene and seal, perform hydrothermal reaction, cool to room temperature, wash, and vacuum dry to constant weight to obtain Ti 3 C 2 T x / MoS 2 Composite materials;

[0027] (3) Ti obtained in step (2) 3 C 2 T x / MoS 2 The composite material is dispersed in DMF and stirred for 20 to 40 minutes. Then, toluene-2,4-diisocyanate (TDI) is added under nitrogen protection, stirred at 70 to 80°C for 5 to 9 hours, centrifuged, washed, and vacuum dried to constant weight to obtain TDI-modified Ti 3 C 2 T x / MoS 2 Composite materials.

[0028] Preferably, in step (1), the drying is performed by vacuum drying at 60 to 90° C. for 10 to 14 hours.

[0029] Further preferably, in step (2), the molybdate is one of ammonium molybdate, potassium molybdate and sodium molybdate; the sulfur source is thiourea; the Ti 3 C 2 T x , molybdate and thiourea ratio is: 100g:30mmol:15~30mmol.

[0030] Further preferably, in step (2), the hydrothermal reaction is carried out at 180-220°C for 16-24h; and the vacuum drying temperature is 60-90°C.

[0031] More preferably, in step (3), the Ti 3 C 2 T x / MoS 2 The mass ratio of the composite material to TDI is 1:8-12.

[0032] Based on the above-mentioned method for preparing an anti-aging and low-temperature resistant glue, the preparation method comprises the following steps:

[0033] Add polyether polyol, castor oil and 2-hydroxyethyl ricinoleate to the reactor, stir evenly, then add plasticizer and isocyanate and continue stirring for 20 to 40 minutes, then add half of dibutyltin dilaurate under nitrogen protection, continue stirring, control the reaction temperature at 75 to 85°C, react for 2 to 4 hours to obtain a polyurethane prepolymer; then add TDI-modified Ti 3 C 2 T x / MoS 2 The composite material and the silane coupling agent are stirred at a speed of 500 to 700 rpm for 20 to 40 minutes, and then the remaining dibutyltin dilaurate is added and stirred for 10 to 30 minutes to obtain an anti-aging and low-temperature resistant glue.

[0034] Based on the application of the anti-aging and low-temperature resistant glue in pasting materials.

[0035] The present invention has the following beneficial effects:

[0036] By adding castor oil and 2-hydroxyethyl ricinoleate to the glue, the low temperature resistance of the glue is improved through the compounding of the two, and the low temperature resistance of the glue is improved by combining with TDI modified Ti 3 C 2 T x / MoS 2 The composite material improves the mechanical properties of the glue, among which Ti 3 C 2 T x / MoS 2 The TDI modification treatment improves its dispersibility in the glue, and the interaction between TDI and the base material further improves the mechanical properties. The anti-aging and low-temperature resistant glue prepared by the present invention has excellent low-temperature resistance and strong mechanical properties. DETAILED DESCRIPTION

[0037] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0038] The isocyanate is diphenylmethane-4,4′-diisocyanate, the polyether polyol is polyether polyol 450, the plasticizer is phthalate, the silane coupling agent is KH-560, and the antioxidant is antioxidant 1010.

[0039] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0040] Example 1

[0041] An anti-aging and low-temperature resistant glue, comprising the following components by weight:

[0042] Isocyanate 70 parts;

[0043] 80 parts of polyether polyol;

[0044] TDI modified Ti 3 C 2 T x / MoS 2 5 parts of composite materials;

[0045] 4 parts castor oil;

[0046] 2 parts of 2-hydroxyethyl ricinoleate;

[0047] 35 parts of plasticizer;

[0048] 4 parts of dibutyltin dilaurate;

[0049] Silane coupling agent 6 parts;

[0050] 2 parts of anti-aging agent;

[0051] TDI modified Ti 3 C 2 T x / MoS 2 The method for preparing the composite material comprises the following steps:

[0052] (1) Weigh 50g Ti 3 AlC 2 Add to 80 mL 45 wt% HF solution, stir for 20 h, filter, wash, and dry in vacuum at 80 °C for 12 h to obtain Ti 3 C 2 T x ;

[0053] (2) 100 g of Ti obtained in step (1) was added 3 C 2 T x Disperse into 250 mL of deionized water, sonicate for 30 min, then add 30 mmol of ammonium molybdate and continue sonication for 15 min, then add 25 mmol of thiourea and continue sonication for 20 min, then transfer to a hydrothermal reactor lined with polytetrafluoroethylene and seal, hydrothermally react at 200 ° C for 20 h, cool to room temperature, wash, and vacuum dry at 80 ° C to constant weight to obtain Ti 3 C 2 T x / MoS 2 Composite materials;

[0054] (3) 10 g of Ti obtained in step (2) 3 C2 T x / MoS 2 The composite material was dispersed in 250 mL DMF and stirred for 30 min. Then, 100 g of toluene-2,4-diisocyanate (TDI) was added under nitrogen protection, stirred at 75 °C for 7 h, centrifuged, washed, and vacuum dried at 80 °C to constant weight to obtain TDI-modified Ti 3 C 2 T x / MoS 2 Composite materials.

[0055] A method for preparing an anti-aging and low-temperature resistant glue comprises the following steps:

[0056] Add polyether polyol, castor oil and 2-hydroxyethyl ricinoleate to the reactor, stir evenly, then add plasticizer and isocyanate and continue stirring for 30 minutes, then add half of dibutyltin dilaurate under nitrogen protection, continue stirring, control the reaction temperature at 80°C, react for 3 hours to obtain a polyurethane prepolymer; then add TDI-modified Ti 3 C 2 T x / MoS 2 The composite material and the silane coupling agent were stirred at a speed of 600 rpm for 30 minutes, and then the remaining dibutyltin dilaurate was added and stirred for 20 minutes to obtain an anti-aging and low-temperature resistant glue.

[0057] Example 2

[0058] An anti-aging and low-temperature resistant glue, comprising the following components by weight:

[0059] 80 parts of isocyanate;

[0060] 70 parts of polyether polyol;

[0061] TDI modified Ti 3 C 2 T x / MoS 2 Composite material 7 parts;

[0062] 3 parts castor oil;

[0063] 3 parts of 2-hydroxyethyl ricinoleate;

[0064] 30 parts of plasticizer;

[0065] 5 parts of dibutyltin dilaurate;

[0066] Silane coupling agent 4 parts;

[0067] 3 parts of anti-aging agent;

[0068] TDI modified Ti 3 C 2 T x / MoS 2 The method for preparing the composite material comprises the following steps:

[0069] (1) Same as Example 1;

[0070] (2) 100 g of Ti obtained in step (1) was added 3 C 2 T x Disperse into 250 mL of deionized water, sonicate for 40 min, then add 30 mmol of potassium molybdate and continue sonication for 10 min, then add 30 mmol of thiourea and continue sonication for 30 min, then transfer to a hydrothermal reactor lined with polytetrafluoroethylene and seal, hydrothermally react at 220 ° C for 16 h, cool to room temperature, wash, and vacuum dry at 90 ° C to constant weight to obtain Ti 3 C 2 T x / MoS 2 Composite materials;

[0071] (3) 10 g of Ti obtained in step (2) 3 C 2 T x / MoS 2 The composite material was dispersed in 250 mL DMF and stirred for 40 min. Then, 120 g of toluene-2,4-diisocyanate (TDI) was added under nitrogen protection, stirred at 80 °C for 5 h, centrifuged, washed, and vacuum dried at 90 °C to constant weight to obtain TDI-modified Ti 3 C 2 T x / MoS 2 Composite materials.

[0072] The preparation method of an anti-aging and low-temperature resistant glue is the same as that of Example 1.

[0073] Example 3

[0074] An anti-aging and low-temperature resistant glue, comprising the following components by weight:

[0075] Isocyanate 60 parts;

[0076] 90 parts of polyether polyol;

[0077] TDI modified Ti 3 C 2 T x / MoS 2 3 parts of composite material;

[0078] 5 parts of castor oil;

[0079] 1 part of 2-hydroxyethyl ricinoleate;

[0080] 40 parts of plasticizer;

[0081] 3 parts of dibutyltin dilaurate;

[0082] Silane coupling agent 8 parts;

[0083] 1 part of anti-aging agent;

[0084] TDI modified Ti 3 C 2 T x / MoS 2 The method for preparing the composite material comprises the following steps:

[0085] (1) Same as Example 1;

[0086] (2) 100 g of Ti obtained in step (1) was added 3 C 2 T x Disperse in 250 mL of deionized water, sonicate for 20 min, then add 30 mmol of sodium molybdate and continue sonication for 20 min, then add 15 mmol of thiourea and continue sonication for 10 min, then transfer to a hydrothermal reactor lined with polytetrafluoroethylene and seal, hydrothermally react at 180 ° C for 24 h, cool to room temperature, wash, and vacuum dry at 60 ° C to constant weight to obtain Ti 3 C 2 T x / MoS 2 Composite materials;

[0087] (3) 10 g of Ti obtained in step (2) 3 C 2 T x / MoS 2 The composite material was dispersed in 250 mL DMF and stirred for 20 min. Then, 80 g of toluene-2,4-diisocyanate (TDI) was added under nitrogen protection, stirred at 70 °C for 9 h, centrifuged, washed, and vacuum dried at 60 °C to constant weight to obtain TDI-modified Ti 3 C 2 T x / MoS 2 Composite materials.

[0088] The preparation method of an anti-aging and low-temperature resistant glue is the same as that of Example 1.

[0089] Comparative Example 1

[0090] The difference between Comparative Example 1 and Example 1 is that an equal amount of castor oil is used to replace 2-hydroxyethyl ricinoleate.

[0091] Comparative Example 2

[0092] The difference between Comparative Example 2 and Example 1 is that the same amount of Ti 3 C 2 T x / MoS 2 Composite materials replace TDI modified Ti 3 C 2 T x / MoS 2 Composite material, the Ti 3 C 2 T x / MoS 2 The method for preparing the composite material comprises the following steps:

[0093] (1) Weigh 50g Ti 3 AlC 2 Add to 80 mL 45 wt% HF solution, stir for 20 h, filter, wash, and dry in vacuum at 80 °C for 12 h to obtain Ti 3 C 2 T x ;

[0094] (2) 100 g of Ti obtained in step (1) was added 3 C 2 T x Disperse into 250 mL of deionized water, sonicate for 30 min, then add 30 mmol of ammonium molybdate and continue sonication for 15 min, then add 25 mmol of thiourea and continue sonication for 20 min, then transfer to a hydrothermal reactor lined with polytetrafluoroethylene and seal, hydrothermally react at 200 ° C for 20 h, cool to room temperature, wash, and vacuum dry at 80 ° C to constant weight to obtain Ti 3 C 2 T x / MoS 2 Composite materials.

[0095] Comparative Example 3

[0096] The difference between Comparative Example 3 and Example 1 is that the same amount of TDI-modified Ti 3 C 2 T x Composite materials replace TDI modified Ti 3 C 2 T x / MoS 2 Composite material, the TDI modified Ti 3 C 2 T x The method for preparing the composite material comprises the following steps:

[0097] (1) Same as Example 1;

[0098] (2) 10 g of Ti obtained in step (1) was added 3 C 2 T x The composite material was dispersed in 250 mL DMF and stirred for 40 min. Then, 120 g of toluene-2,4-diisocyanate (TDI) was added under nitrogen protection, stirred at 80 °C for 5 h, centrifuged, washed, and vacuum dried at 90 °C to constant weight to obtain TDI-modified Ti 3 C 2 T x Composite materials.

[0099] The comprehensive performance of Examples 1-3 and Comparative Examples 1-3 was tested, and the specific test results are shown in Table 1.

[0100] Among them, peel strength: GB / T 532-2008;

[0101] Table 1

[0102]

[0103]

[0104] It can be seen from Table 1 that the anti-aging and low-temperature resistant glue prepared by the present invention has excellent low-temperature resistance. Moreover, by comparing Example 1 with Comparative Example 1, it can be seen that the present invention improves the low-temperature resistance of the glue by adding castor oil and 2-hydroxyethyl ricinoleate and utilizing the mutual relationship between the two. 3 C 2 T x / MoS 2 The composite material improves the performance of the glue. It can be seen that the anti-aging and low-temperature resistant glue prepared by the present invention has strong low-temperature resistance and is widely used.

[0105] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An anti-aging and low-temperature resistant glue, characterized by: By weight, it includes the following components: 60-80 parts of isocyanate; 70-90 parts of polyether polyol; TDI modified Ti3C2T x / MoS2 composite material 3 to 7 parts; 3-5 parts of castor oil; 1-3 parts of 2-hydroxyethyl ricinoleate; 30-40 parts of plasticizer; 3-5 parts of dibutyltin dilaurate; Silane coupling agent 4-8 parts; 1 to 3 parts of anti-aging agent.

2. The anti-aging and low-temperature resistant glue according to claim 1, characterized in that: The isocyanate is diphenylmethane-4,4′-diisocyanate; and the polyether polyol is polyether polyol 450.

3. The anti-aging and low-temperature resistant glue according to claim 1, characterized in that: The plasticizer is phthalate; the silane coupling agent is KH-560; and the anti-aging agent is antioxidant 1010.

4. The anti-aging and low-temperature resistant glue according to claim 1, characterized in that: The TDI-modified Ti3C2T x The preparation method of the / MoS2 composite material comprises the following steps: (1) Etch the Ti3AlC2 precursor with concentrated HF solution to obtain Ti3C2T x Dispersion, separation, washing, drying to Ti3C2T x ; (2) The Ti3C2T obtained in step (1) x Disperse in deionized water, ultrasonicate for 20-40 min, then add molybdate and continue ultrasonication for 10-20 min, then add sulfur source and continue ultrasonication for 10-30 min, then transfer to a hydrothermal reactor lined with polytetrafluoroethylene and seal, perform hydrothermal reaction, cool to room temperature, wash, and vacuum dry to constant weight to obtain Ti3C2T x / MoS2 composite materials; (3) The Ti3C2T obtained in step (2) x The Ti3C2T / MoS2 composite material was dispersed in DMF and stirred for 20-40 min. Then, toluene-2,4-diisocyanate (TDI) was added under nitrogen protection and stirred at 70-80 °C for 5-9 h. The mixture was centrifuged, washed, and vacuum dried to constant weight to obtain TDI-modified Ti3C2T x / MoS2 composite materials.

5. The anti-aging and low-temperature resistant glue according to claim 4, characterized in that: In step (1), the drying is performed by vacuum drying at 60 to 90° C. for 10 to 14 hours.

6. The anti-aging and low-temperature resistant glue according to claim 4, characterized in that: In step (2), the molybdate is one of ammonium molybdate, potassium molybdate and sodium molybdate; the sulfur source is thiourea; the Ti3C2T x , molybdate and thiourea ratio is: 100g:30mmol:15~30mmol.

7. The anti-aging and low-temperature resistant glue according to claim 4, characterized in that: In step (2), the hydrothermal reaction is carried out at 180-220° C. for 16-24 hours; and the vacuum drying temperature is 60-90° C.

8. The anti-aging and low-temperature resistant glue according to claim 4, characterized in that: In step (3), the Ti3C2T x The mass ratio of / MoS2 composite material to TDI is 1:8~12.

9. The method for preparing an anti-aging and low-temperature resistant glue according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: Add polyether polyol, castor oil and 2-hydroxyethyl ricinoleate to the reactor, stir evenly, then add plasticizer and isocyanate and continue stirring for 20-40 minutes, then add half of dibutyltin dilaurate under nitrogen protection, continue stirring, control the reaction temperature at 75-85°C, react for 2-4 hours to obtain a polyurethane prepolymer; then add TDI-modified Ti3C2T x / MoS2 composite material and silane coupling agent, stir at a speed of 500-700 rpm for 20-40 min, then add the remaining dibutyltin dilaurate, and continue stirring for 10-30 min to obtain an anti-aging and low-temperature resistant glue.

10. Use of the anti-aging and low-temperature resistant glue according to any one of claims 1 to 9 in pasting materials.

Citation Information

Patent Citations

  • Polymer used for electric sealing glue, and preparation method thereof

    CN108165226A

  • Double-component polyurethane glue and preparation method thereof

    CN113897166A

  • Preparation method and application of biosensor based on three-dimensional titanium carbide-molybdenum disulfide compound

    CN111766290A

  • Two-component polyurethane pouring sealant as well as preparation method and application thereof

    CN117701220A

  • Polyurethane heat-conducting structural adhesive and preparation method thereof

    CN118064102A